1996
DOI: 10.1093/infdis/174.supplement_1.s98
|View full text |Cite
|
Sign up to set email alerts
|

Group A Rotavirus Veterinary Vaccines

Abstract: Group A rotaviruses cause diarrhea in young livestock and poultry; consequently, vaccination strategies have focused on induction of active or passive immunity. Gnotobiotic pigs and calves serve as useful models to evaluate induction of active immunity by candidate animal or human rotavirus vaccines. However, live attenuated rotavirus vaccines lacked efficacy when administered orally to calves and pigs in the field, presumably because colostral antibodies inhibited vaccine virus replication. The widespread occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
107
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 54 publications
3
107
1
1
Order By: Relevance
“…Similar to findings in humans, RVA is also one of the most frequently detected enteropathogens associated with acute enteritis among young farm animals such as piglets and calves. RVA infections pose an economic threat to the livestock industry due to increased morbidity and mortality rates, and poor growth performance (8,20,35). Although implementing and maintaining appropriate health management practices are obviously crucial for controlling RVA-induced diarrhea in piglets and calves (8,43), there is a lack of understanding of the viral ecology within these meat animals from birth to harvest.…”
mentioning
confidence: 99%
“…Similar to findings in humans, RVA is also one of the most frequently detected enteropathogens associated with acute enteritis among young farm animals such as piglets and calves. RVA infections pose an economic threat to the livestock industry due to increased morbidity and mortality rates, and poor growth performance (8,20,35). Although implementing and maintaining appropriate health management practices are obviously crucial for controlling RVA-induced diarrhea in piglets and calves (8,43), there is a lack of understanding of the viral ecology within these meat animals from birth to harvest.…”
mentioning
confidence: 99%
“…These infections lead to approximately 527,000 deaths each year, the vast majority occurring in developing countries (33). RVs are also responsible for gastroenteritis in many other animal species, notably mammals and birds (16,38). RVs are members of the family Reoviridae and possess a genome consisting of 11 segments of double-stranded RNA (dsRNA).…”
mentioning
confidence: 99%
“…Rotaviruses are an important cause of gastroenteritis in numerous species of animals, including humans (28), where these viruses represent the primary causative agent of life-threatening dehydrating diarrhea in children under the age of 5 (20). Early studies revealed that the growth of rotavirus is restricted in IFN-treated cells, but less so than other viruses, such as vesicular stomatitis virus (VSV) and reovirus (19), which are noted for their increased susceptibility to the antiviral effects of IFN.…”
mentioning
confidence: 99%